Russia's postcolonial identity : a subaltern empire in a Eurocentric world - Morozov, Viatcheslav (Central and Eastern European Perspectives on International Relations, 2015)
01 02 This book applies postcolonial theory to Russia by looking at it as a subaltern empire. It pushes postcolonial studies and constructivist International Relations towards an uneasy dialogue, which produces tensions and reveals multiple blind spots in both approaches. A critical re-evaluation of the existing literature enables the author to produce a comprehensive account of how Russia's position in the international system has conditioned its domestic development, and how this in turn generated specific foreign policy outcomes. Having internalised the Eurocentric worldview, Russia is nevertheless different from the core European countries. This difference is not determined by 'culture', but rather by uneven and combined development of global capitalism, in which Russia is integrated as a semi-peripheral nation. The Russian state has colonised its own periphery on behalf of the Western core, but has never been able to overcome economic and normative dependency on the West. The peculiar dialectic of the subaltern and the imperial during the post-Soviet period has given rise to a regime which claims to defend 'genuine Russian values', while in fact there is nothing behind this new traditionalism but the negation of Western hegemony. Trying to 'defend' the nation from the postulated threat of Western interventionism, the regime engages in a disavowal of politics and thus suppresses popular subjectivity. The only political subject that remains on the horizon of Russian politics is the West, while the Russian people, as any other subaltern, are being spoken for, and thus silenced, by the country's Eurocentric elites and the Western intellectuals. 02 02 Pushing postcolonial studies and constructivist International Relations towards an uneasy dialogue, this book looks at Russia as a subaltern empire. It demonstrates how the dialectic of the subaltern and the imperial has produced a radically anti-Western regime, which nevertheless remains locked in a Eurocentric outlook. 04 02 1. The Postcolonial and the Imperial in the Space and Time of World Politics 2. Russia in/and Europe: Sources of Ambiguity 3. Material Dependency: Postcolonialism, Development and Russia's 'Backwardness' 4. Normative Dependency: Putinite Paleoconservatism and the Missing Peasant 5 The People are Speechless: Russia, the West and the Voice of the Subaltern 6. Conclusion 13 02 Viatcheslav Morozov is Professor of EU-Russia Studies at the University of Tartu. Before moving to Estonia in 2010, he taught for thirteen years at the St Petersburg State University, Russia. He is the author of Russia and the Others: Identity and Boundaries of a Political Communit y and the editor of Decentring the West: The Idea of Democracy and the Struggle for Hegemony .